2011
DOI: 10.3171/2010.5.jns091972
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative seizures following the resection of convexity meningiomas: are prophylactic anticonvulsants indicated?

Abstract: While it is thought that the routine use of prophylactic antiepileptics may prevent new seizures in patients undergoing surgery for a convexity meningioma, the rate of new seizures in untreated patients is probably very low. Data in this study call into question whether the cost and side effects of these medications are worth the small benefit their administration may confer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…In addition, in a 2010 single center teaching hospital in Alberta, Lwu et al found the rate of seizure prophylaxis to be 27% [15] . Deviation from the guideline recommendations may be attributed to the perceived harms of seizures on the patients' psychosocial and physical well-being, especially during the immediate post-operative period where the risk of seizures is known to be higher [6,18,20] . Our center revealed a 28% prophylaxis rate overall, which is similar to the prophylaxis rate found by Lwu and colleagues in Alberta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a 2010 single center teaching hospital in Alberta, Lwu et al found the rate of seizure prophylaxis to be 27% [15] . Deviation from the guideline recommendations may be attributed to the perceived harms of seizures on the patients' psychosocial and physical well-being, especially during the immediate post-operative period where the risk of seizures is known to be higher [6,18,20] . Our center revealed a 28% prophylaxis rate overall, which is similar to the prophylaxis rate found by Lwu and colleagues in Alberta.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the incidence and severity of AED related side effects were noted to be higher in brain tumour patients compared to a general population of patients receiving AEDs [7] . Subsequent metaanalyses and systematic reviews conducted after the release of these guidelines further support this recommendation [5,12,13,18,19] . One of the major limitations in interpreting the available evidence is that many patients who experienced seizures while receiving AED prophylaxis had sub-therapeutic levels.…”
Section: Analysis Of the Adherence To Seizure Prophylaxis Guidelines mentioning
confidence: 91%
“…In a study of 121 patients undergoing glioma surgery, despite consistent perioperative AED prophylaxis, 9.1% of patients experienced a seizure within the first postoperative week, and problems with drug tolerability were not uncommon . In another observational series on meningioma surgery without seizure history, there was one single postoperative seizure in the group of 51 patients on AED prophylaxis and no seizures in 129 patients who did receive prophylaxis, suggesting little difference in seizure risk (Sughrue et al, 2011). Therefore, while AED prophylaxis remains commonly prescribed in patients with brain tumors (Siomin et al, 2005;Riva et al, 2006;Rosati et al, 2009;Lwu et al, 2010), the majority of evidence and clinical guidelines advise against this practice, and the application of perioperative prophylaxis will require further investigation.…”
Section: Prophylactic Aed Usementioning
confidence: 99%
“…While it is universally recognized that preoperative seizures must be controlled with AED administration, 25 significant controversy surrounds the use of perioperative AED prophylaxis for patients undergoing brain tumor resection with no seizure history. 58 A prophylactic drug should only be given if the risk of the adverse outcome (i.e., a seizure) is prominent and the medication is both effective at preventing it and poses an acceptable risk of toxicity. 25 The American Academy of Neurology released practice parameters in 2000 advising against AED prophylaxis in newly diagnosed brain tumor patients due to a lack of efficacy and heightened adverse effects in their meta-analysis.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…15 While historical series demonstrated effective seizure prevention using AEDs following craniotomy, 42,43 recent data suggest a low baseline incidence of postoperative seizures even in the absence of AED prophylaxis. 26,58 The purpose of this study was to critically analyze the literature to select the current best available evidence. Personal preference heavily influences decision making on AED use following brain tumor surgery, 58 perhaps an indication that the literature has not been translated into treatment recommendations for clinical practice.…”
Section: ©Aans 2014mentioning
confidence: 99%